PENGEMBANGAN EVALUASI PEMBELAJARAN MATEMATIKA BERBASIS WORDWALL PADA MATERI BANGUN RUANG SISI DATAR - Yusra, Isna; Reflina, Reflina (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
In order to maximize the learning interest capacity of class VIII MTSS Al-Washliyah Tembung pupils for the 2023–2024 academic year, this research attempts to deepen the mathematics learning assessment technique utilizing Wordwall on flat-sided geometric material. Students might find the evaluation process more engaging and enjoyable when technology-based assessment formats like Wordwall are used. Using the ADDIE model approach (Analysis, Design, Development, Implementation and assessment), a development study was employed as the research technique to create a Wordwall-based mathematics learning assessment. Observation, surveys, interviews, and documentation are some of the techniques used to collect data. Techniques for analyzing data include validity, usefulness, and effectiveness analysis. The project yielded a Wordwall-based evaluation product for mathematics learning on flat-sided geometric material. Four validators gave this product an average score of 93%, which was used to declare it legitimate. This product received an 88% practicality grade after being provided practically by practitioners. The N-gain test scored 0.66 in the medium group based on the outcomes of the Wordwall-based learning assessment test. In summary, the assessment of Wordwall-based mathematics instruction using flat-sided geometric materials for MTSS Al-Washliyah Tembung's class VIII.